LEGAL ACCOUNTABILITY OF THE OFFICIAL MAKING LAND DEEDS IN UNAUTHORIZED LAND RIGHTS TRANSFERS: A CASE STUDY OF SHM 24451 - Fanny Fernian Yahya Artikasari; Isharyanto; Rahayu Subekti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to examine the legal accountability of the Land Deed Official (PPAT) in unauthorized land rights transfers in the case study of SHM 24451. In their function as a public authority, the PPAT, creates authentic deeds, particularly deeds of land rights transfer, which serve as evidence proving that a legal act of rights transfer has occurred lawfully and provides legal certainty. This research is normative juridical legal research using doctrinal, conceptual, and case approaches. A descriptive method is used to analyze data based on the theory of authentic deeds and the theory of official accountability. The problem arises when, during the deed-making process, there is suspicion of non-compliance with formal and material requirements, thus making the PPAT, as a public official, accountable for the legal acts performed. The results indicate that rights transfers that do not meet formal and material requirements can be subject to administrative, civil, and criminal liabilities. This causes legal violations and harms the community. These findings emphasize the importance of compliance with professional ethics, legal principles during the execution of tasks, authority as a PPAT, as well as maintaining the integrity of the profession, institution, and public trust.